2016
DOI: 10.1016/j.wasman.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of parameters influencing methane generation due to biodegradation of municipal solid waste in landfills and laboratory experiments

Abstract: The energy conversion potential of municipal solid waste (MSW) disposed of in landfills remains largely untapped because of the slow and variable rate of biogas generation, delayed and inefficient biogas collection, leakage of biogas, and landfill practices and infrastructure that are not geared toward energy recovery. A database consisting of methane (CH4) generation data, the major constituent of biogas, from 49 laboratory experiments and field monitoring data from 57 landfills was developed. Three CH4 gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 69 publications
0
20
0
1
Order By: Relevance
“…Here, both L 0 and k have been determined by waste composition to compare results of single-phase and multiphase models. Calculating k based solely on waste composition, similar to the calculation of DOC or L 0 , implies that L 0 and k are directly related (Fei et al, 2015). However, research attempting to fit estimated gas generation to modeled results has shown that L 0 and k are inversely related (Tolaymat et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Here, both L 0 and k have been determined by waste composition to compare results of single-phase and multiphase models. Calculating k based solely on waste composition, similar to the calculation of DOC or L 0 , implies that L 0 and k are directly related (Fei et al, 2015). However, research attempting to fit estimated gas generation to modeled results has shown that L 0 and k are inversely related (Tolaymat et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Normalmente, estes modelos dividem os resíduos sólidos urbanos (RSU) em várias categorias, cada uma com seu respectivo potencial de geração de metano (L) a partir da biodegradação de RSU e constante de biodegradação (k) (MACHADO et al, 2009;MOU;KJELDSEN, 2015;FEI;ZEKKOS;RASKIN, 2016 et al, 2009;MACIEL & JUCÁ, 2011;SCHEUTZ et al, 2011;ABREU, 2014;MOREIRA & CANDIANI, 2016 ). T(t' ,t) pode ser chamada de função resposta do aterro sanitário quanto à produção de metano, já que fornece a taxa de geração ao longo do tempo causada por uma deposição unitária de RSU.…”
Section: Evaluation Of Kinetic Parameters For Methane Generation In Aunclassified
“…This model requires data related to the average annual rate of waste disposed, the number of years the landfill has been or was open, the number of years that the landfill has been closed, the potential of waste disposed to generate methane and the rate of methane generation of the waste disposed [16]. The estimate of methane generated by the first order equation is expressed as follows [17]:…”
Section: Epa Modelmentioning
confidence: 99%